He s got the touch : Tracing the masculine regulation of the body schema in reciprocal relations between self-others-things' - Murphy, Stephen (My University, 2022)
The purpose of this article is to examine the interconnections between embodiment and masculinity. Departing from the predominant discursive view of masculinity, I explain how a phenomenological, post-dualistic approach, inspired by Merleau-Ponty and Butler, can be mobilized to conceptualize masculinity as an embodied, performative accomplishment that reverberates around socio-material relations. Towards this end, this article traces the masculine regulation of the body schema as it develops in reciprocal relations between ‘self-others-things’. Drawing from reflexive field notes and participant interviews, gathered over a 5-year period of observant participation with male motorcycle repairers, the article shows machinic masculinity as an embodied emplacement that is constituted by socio-material entanglements and performative enactments. In so doing, the article conceptually reframes how masculinity and embodiment are understood in Consumer Culture Theory (CCT).
PUBLISHED
Keywords: Body schema; Embodiment; Emplacement; Judith Butler; Machinic masculinity; Masculinity; Merleau-Ponty; Motorcycle repair; Performativity; Phenomenology; Tinkering; Identities in Transformation; Consumer behaviour, society; Culture; Gender